Water research in support of the Sustainable Development Goal 6: A case study in Belgium. (20th December 2020) - Ho, Long; Alonso, Alice; Eurie Forio, Marie Anne; Vanclooster, Marnik; Goethals, Peter L.M.
Abstract: Reaching the Sustainable Development Goal (SDG) 6 on water and sanitation is fundamentally important and conditional to the achievement of all the other SDGs. Nonetheless, achieving this goal by 2030 is challenging, especially in the Global South. Science lies at the root of sustainable development and is a key to new solutions for addressing SDG 6. However, SDG 6-related scientific outputs are often unknown, forming disconnections between academic world and practitioners implementing solutions. This study proposed a bibliometric and text mining method to qualitatively and quantitatively characterize the contribution of water research to the achievement of SDG 6. The method was applied for water research produced by Belgian-affiliated authors with a focus on the Global South collaboration. Despite accounting for less than one percent of the total global publications, Belgian water research has had a relatively high publication rate compared to its neighboring countries. We observed longstanding collaborations between Belgian and scientists from worldwide countries, and an increasing collaboration rate with countries from the Global South. The biggest share of publications focused on topics related to the targets 6.3, 6.4, 6.5, and 6.6, with the main hotspots for Belgian water research being water treatment, water stress, water pollution, climate change, and water modeling. The findings of the bibliometric search have been integrated into an online, user-friendly dashboard to facilitate the identification of research body and experts for practitioners and policy makers. The presented methodology is sufficiently generic and can be used to optimize other science programs in relation to the 2030 Agenda in other countries and regions. In this case study, the findings support shaping the Belgian cooperation and development policy in the water sector, and creating appropriate synergies between Belgian water researchers and their counterparts in the Global South. Highlights: New method to extract and analyze the publications supporting SDG 6 & its targets. Belgian water research had a high publication rate compared to its neighbors. A raising collaboration rate between Belgium and the Global South countries. Biggest share of Belgian water research has focused on targets 6.3, 6.4, 6.5 & 6.6 Findings and dashboard are important for optimizing the development of SDGs.